Optimal pricing and service capacity management for a matching queue problem with loss-averse customers. (3rd October 2021) - Jiang, Tao; Chai, Xudong; Liu, Lu; Lv, Jun; Ammar, Sherif I.
Abstract : This study examines a matching queue problem (double-sided matching queue) where customers are loss-averse with respect to their waiting times. We first set the reference point and construct the loss-averse customers' utility function, then we investigate the customers' strategic behaviour regarding their joining or balking dilemma, with reference to the information unavailable. Next, we derive the service providers' optimal pricing and capacity-sizing decisions. We find that compared to the fully rational customers, the loss-averse behaviour could reduce the joining probability of customers and drive down the service price. Furthermore, the profit function of the service providers could be a unimodal function of the servers queue capacity size, with the servers' optimal queue capacity size increasing with the increase in the degree of the customers' loss aversion. Moreover, different potential market sizes may lead to different values of the profit, that is, under different levels of the customers' arrival rate, the service providers should make a reasonable and timely adjustment for the servers queue capacity size to guarantee their profits.